Direct Visualization of Asymmetric Adenine Nucleotide-Induced Conformational Changes in MutLα - Sacho, Elizabeth J (2008)
MutLα, the heterodimeric eukaryotic MutL homolog, is required for DNA mismatch repair (MMR) in vivo. It has been suggested that conformational changes, modulated by adenine nucleotides, mediate the interactions of MutLα with other proteins in the MMR pathway, coordinating the recognition of DNA mismatches by MutSα and the activation of MutLα with the downstream events that lead to repair. Thus far, the only evidence for these conformational changes has come from x-ray crystallography of isolated domains, indirect biochemical analyses, and comparison to other members of the GHL ATPase family to which MutLα belongs. Using atomic force microscopy (AFM), coupled with biochemical techniques, we demonstrate that adenine nucleotides induce large asymmetric conformational changes in full-length yeast and human MutLα, and that these changes are associated with significant increases in secondary structure. These data reveal an ATPase cycle where sequential nucleotide binding, hydrolysis, and release modulate the conformational states of MutLα.